Ginsenoside compound K induces ferroptosis via the FOXO pathway in liver cancer cells - Jiaxin Chen; Zhuoshi Wang; Jinghao Fu; Yuesong Cai; Haoyi Cheng; Xinmu Cui; Manqing Sun; Mingyue Liu; Xuewu Zhang (BMC, 2024)
Abstract Liver cancer is a common malignant tumor worldwide, traditional Chinese medicine is one of the treatment measures for liver cancer because of its good anti-tumor effects and fewer toxic side effects. Ginsenoside CK (CK) is an active component of ginseng. This study explored the mechanism by which CK induced ferroptosis in liver cancer cells. We found that CK inhibited the proliferation of HepG2 and SK-Hep-1 cells, induced ferroptosis of cells. Ferrostatin-1, an ferroptosis inhibitor, was used to verify the role of CK in inducing ferroptosis of liver cancer cells. Network pharmacological analysis identified the FOXO pathway as a potential mechanism of CK, and western blot showed that CK inhibited p-FOXO1. In cells treated with the FOXO1 inhibitor AS1842856, further verify the involvement of the FOXO pathway in regulating CK-induced ferroptosis in HepG2 and SK-Hep-1 cells. A HepG2 cell-transplanted tumor model was established in nude mice, and CK inhibited the growth of transplanted tumors in nude mice, p-FOXO1 was decreased in tumor tissues, and SLC7A11 and GPX4 expressions were also down-regulated after CK treatment. These findings suggested that CK induces ferroptosis in liver cancer cells by inhibiting FOXO1 phosphorylation and activating the FOXO signaling pathway, thus playing an antitumor role.